2021
DOI: 10.1177/13524585211014760
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of T1/T2-weighted ratio in detection of cortical demyelination is similar to magnetization transfer ratio using post-mortem MRI

Abstract: Background: Detecting cortical demyelination using magnetic resonance imaging (MRI) in multiple sclerosis (MS) remains a challenge. Magnetization transfer ratio (MTR), T1-weighted/T2-weighted ratio (T1T2R), and T2-weighted (T2w) signal are sensitive to cortical demyelination, but their accuracy is unknown. Objectives: To quantify the sensitivity, specificity, and accuracy of postmortem T1T2R, MTR, and T2w in detecting cortical demyelination. Methods: In situ postmortem MRIs from 9 patients were used to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Two studies ( Righart et al, 2017 , Nakamura et al, 2017 ) demonstrated correlations between reduced values and tissue damage, although in different topographies and pathological substrates: in demyelinated cortex correlating with myelin density, and in cortical NAGM correlating with dendrite density. Still on histological validation at the cortical level, despite a good sensitivity to detect cortical demyelination, a modest T1-w/T2-w ratio specificity was demonstrated in a recent work ( Zheng et al, 2022 ). In addition to the cerebral cortex, in two other studies focusing on different subcortical regions, ( Arshad et al, 2017 , Uddin et al, 2019 ) T1-w/T2-w ratio has been suggested as a general measure of microstructure, which may be more affected by axonal diameter/density than myelin density.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies ( Righart et al, 2017 , Nakamura et al, 2017 ) demonstrated correlations between reduced values and tissue damage, although in different topographies and pathological substrates: in demyelinated cortex correlating with myelin density, and in cortical NAGM correlating with dendrite density. Still on histological validation at the cortical level, despite a good sensitivity to detect cortical demyelination, a modest T1-w/T2-w ratio specificity was demonstrated in a recent work ( Zheng et al, 2022 ). In addition to the cerebral cortex, in two other studies focusing on different subcortical regions, ( Arshad et al, 2017 , Uddin et al, 2019 ) T1-w/T2-w ratio has been suggested as a general measure of microstructure, which may be more affected by axonal diameter/density than myelin density.…”
Section: Discussionmentioning
confidence: 99%
“…Although within demyelinated cortical lesions, the intensity of the T1w/T2w ratio was demonstrated to be decreased in an early study, 4 a later study concluded that cortical changes other than demyelination influence the T1w/T2w signal. 5 When comparing T1w/T2w values between normalappearing and lesioned tissue in both brain grey and white matter at 7 Tesla, a striking difference was indeed found in white matter, while a difference in grey matter between lesioned and non-lesioned tissue was hardly detectable (i.e. small when compared to control regions and non-significant when compared to whole brain normal-appearing grey matter of controls).…”
mentioning
confidence: 93%
“…Several MRI-pathology correlational studies have been performed using autopsy specimen with in situ imaging examining T1/T2 ratios in the cortex. [7][8][9][10] In those studies, the associations between T1/ T2-weighted ratio and cortical myelin status have been inconclusive. Our study 7 reported significantly different T1/T2-weighted ratios in myelinated versus demyelinated cortical areas (n = 6); Righart et al 9 reported an association with dendritic density but not myelin content nor axonal density (n = 9); and Preziosa et al 8 reported an association between neurite density and T1/T2-weighted ratios (n = 15).…”
mentioning
confidence: 99%
“…The T1/T2-weighted ratio values were measured on the midthickness surface (halfway between white matter and pial surfaces). While the midthickness method is likely the appropriate unbiased method for future in vivo studies, 10 this method may be affected by the normal variances in laminar myelin level or thickness in validation studies. Preziosa et al also found a significant difference in T1/T2-weighted ratios between normal-appearing cortex and demyelinated MS or normal cortex ( p ⩽ 0.007).…”
mentioning
confidence: 99%